(3cJGH aj GdMOjKs ((3CMeO Hf QHjY s)
(3ChdgG (B:s
(3GdMeO ddg , heG Jhajbi EdG HGddg CeG HYO agPG cJGH LeYJg ef YOI cJH , hCcKQ eG GYJeOJ Ydjg ai fbdi eG LeYg YHO GdQMef GHf eNdha GdEeGe GdKYGdHi ai cJGHg GdYdhe GdaGNQI ai CNHGQ GdBNQI Ke cJGH GdSjhWi GdHOhQ GdSGaQI ai Ydhe GdBNQI HGHs
(3BNQgG (B:s
(3abO Qhi GdHNGQi heSde Yf CHj SYjO GdNOQi Cf QShd Gddg bGd jbhd Gddg (B: (3jG Gdg GdLfI , ajbhdhf(B: (3dHjc QHfG hSYOjc , hGdNjQ ai jOjcc , ajbhd (B: (3gd QVjJe ? GfJgi s
(3HgG fXGe GdJYbjHIs
(3cJHgG fGSNgG dCNjg ai Gddg eMeO Hf SYO Hf GdjYbhH cJHJ HYV YHGQGJgG HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdMOjK h GdeUWdMs